Using Remote Sensing and GIS to Investigate the Effect of Urban Sprawl on Health Facilities in Egbeda Local Government Area, Ibadan, Oyo State, Nigeria (Global Journal of Science Frontier Research, 2022)
The rapid rate of urbanization witnessed in the last century has produced more sprawls in the major cities of the world particularly in developing countries where thousands of rural people move into the major cities at large proportion Urban sprawl affects the landscape the ecology of an area travel patterns resource consumption health facilities and water discharge The aim of this research is to use remote sensing and GIS to investigate the effect of urban sprawl on health facilities in Egbeda Local Government Area Oyo State Nigeria with a view to determining how useful such information can be to planners decision makers health sector and private organization for effective urban management and sustainability The research was conducted using remote sensing and Geographical information System at determining the spatial pattern and dynamics of the urban sprawl in Egbeda Local Government Area Oyo State The methods used includes digitization digital image processing and spatial analysis using an inverse distance weighted IDW technique Maximum likelihood supervised classification and post classification change detection techniques were applied to Landsat imageries acquired in 1984 2006 and 2018 Geographical Positioning System GPS was used to identify the health institutions and obtain the coordinates of the location of each identified health facilities These were loaded on the imagery of Egbeda Local Government Area that was digitized from the images using the software of ArcGIS 10 2 Imageries were classified into built-up area vegetation bare surface cultivation and water body The results of the analysis obtained showed drastic change in built-up area which rose to 32 8 from 25 4 between 1984 and 2018 periods To reduce the effect of urban sprawl on health facilities in the study areas the government stakeholders policy makers and urban planner can make use of these techniques for effective city planning and sprawl control to attain and sustain future urban development
Keywords: landuse; land cover; urban management; remote sensing; GIS; satellite imageries